Interacting short-term regulatory mechanisms enable the conversion of light energy to chemical energy in photosynthesis - Tikkanen, Mikko (Journal of experimental botany, 2025)
© The Author(s) 2025. Published by Oxford University Press on behalf of the Society for Experimental Biology.